2018
DOI: 10.3389/fneur.2018.00376
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Rating Scales and Clinical Measures for Screening of Rapid Eye Movement Sleep Behavior Disorder and for Predicting Conversion to Parkinson’s Disease and Other Synucleinopathies

Abstract: Rapid eye movement (REM) sleep behavior disorder (RBD) is characterized by repeated episodes of REM sleep-related vocalizations and/or complex motor behaviors. Definite diagnosis of RBD is based on history and polysomnography, both of which are less accessible due to the lack of trained specialists and high cost. While RBD may be associated with disorders like narcolepsy, focal brain lesions, and encephalitis, idiopathic RBD (iRBD) may convert to Parkinson’s disease (PD) and other synucleinopathies in more tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 137 publications
2
30
0
1
Order By: Relevance
“…Biomarkers capable of predicting the phenoconversion from iRBD to clinical synucleinopathies are of great importance. Previous studies have indicated that the rate of phenoconversion was significantly increased in patients with motor dysfunction, olfactory deficits, mild cognitive impairment, erectile dysfunction, abnormal dopamine transporters scan, color vision abnormalities, and other factors 27,28 . In our study, the methylation level at CpG 17 was able to predict early phenoconversion.…”
Section: Discussionsupporting
confidence: 55%
“…Biomarkers capable of predicting the phenoconversion from iRBD to clinical synucleinopathies are of great importance. Previous studies have indicated that the rate of phenoconversion was significantly increased in patients with motor dysfunction, olfactory deficits, mild cognitive impairment, erectile dysfunction, abnormal dopamine transporters scan, color vision abnormalities, and other factors 27,28 . In our study, the methylation level at CpG 17 was able to predict early phenoconversion.…”
Section: Discussionsupporting
confidence: 55%
“…The cognitive functions of the subjects were evaluated using the Mini-Mental State Examination (MMSE), which is a screening tool for dementia with a cut-off score of 23/24 (maximum score of 30) (50). The participants were asked to answer the REM sleep behavior disorder screening questionnaire (RBDSQ), which consists of 13 questions (maximum possible score = 13), to assess RBD symptoms such as nocturnal movements, injuries, and motor behavior during the night (51,52). In this study, the Japanese version of the RBDSQ (RBDSQ-J) was used (53).…”
Section: Clinical Interviewmentioning
confidence: 99%
“…It consists of 13 tasks and evaluates multiple domains of cognitive function (visuospatial abilities, attention, concentration, language, shortterm and working memory). It can be administered within 15 min and has been used to screen patients with a wide range of conditions including aSAH [19][20][21][22]. The maximum score is 30 points and using a cutoff of 25 points is suggested to detect mild cognitive impairment; therefore, in the current study a MoCA score of 25 or less was categorized as impaired.…”
Section: Montreal Cognitive Assessment (Moca)mentioning
confidence: 99%